Assessment and identification of risk factors associated with avian coccidiosis in Haryana, India - Grakh, Kushal; Mittal, Dinesh; Prakash, Anand; Kumar, Manesh; Kumar, Ramesh; Jindal, Naresh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Coccidiosis caused by protozoan parasite of Eimeria species is one of the most important poultry diseases prevalent in different parts of globe including India. The parasite invades the intestinal cells and the disease is characterised by enteritis and diarrhoea leading to weight loss, altered feed conversion ratio, poor growth and eventually death of affected birds. A survey on commercial poultry farms was conducted in 10 districts of Haryana state, India, using a questionnaire to assess the status of coccidiosis, associated risk factors and management practices followed. On analysis of data, it was found that overall, 15 (28.8%) farms had history of coccidiosis. One-fourth (25%) of the farmers reported the use of anticoccidial drugs for chemoprophylaxis or therapeutic purposes at their farms. Further, on statistical analysis using Chi-square, several factors were found to be statistically significant (p<0.05) with occurrence of coccidiosis at these farms including type of birds, capacity of birds, visitor’s entry, litter removal frequency, number of antibiotics used for treatment and foggers use in summer at farms under study. These factors were identified as predisposing and/ or risk factors associated with occurrence of coccidiosis at the farms. The odds of occurrence of coccidiosis were significantly higher (p<0.001) at the farms with presence of risk factors identified in the study as compared to the farms where risk factors were absent. The present study revealed history of coccidiosis at several poultry farms leading to undue economic burden to farmers. For effective management of coccidiosis at the farms, the use of foggers may be discouraged. Moreover, litter may be turned or removed frequently along with judicious use of anti-coccidiostats or other alternatives may be encouraged.